Gender traits in relation to work versus career salience - Madelyn Geldenhuys; Anita Bosch; Shuaib Jeewa; Ioulia Koutris (SA Journal of Industrial Psychology, 2019)
Orientation: The concepts of work- and career-role salience are used interchangeably, yet work focuses on the short-term aspect and career on the long-term aspect.